Charge Density Distributions, Elastic and Inelastic Electron Scattering Form Factors of 20Ne and 24Mg Nuclei - K. Issa, H.; Flaiyh, Ghaith N. (Iraqi Journal of Physics, 2025)
In this study, the charge density distribution was calculated using the folding model, which has been applied to study the roles upon the center of mass and Pauli pair association affecting the density relying on the efficient two-body interactions, as a formula for the two-body density applicable to limit nuclei may be derived in terms of the pair correlation function for 20Ne and 24Mg nuclei. The elastic electron scattering form factors F(q) and the root of the mean square charge radii were determined. The inelastic longitudinal electron scattering form factors associated with the isosceles transitioning T = 0 of the (  ) and ( ) for the 20Ne and 24Mg nuclei were determined. A wave function within the model space, which is defined by the orbits   ,  and , is unable to produce an acceptable form factor. Using the folding model to estimate the lower state form for the distribution of charge density and adopting the shape of the Tassie model, the core polarization transition density is calculated. An astounding understanding of the computed inelastic longitudinal F(q)'s and those of observational data is seen for all investigated nuclei, and it is noted that the core polarization effects, which reflect the group modes, are crucial to this outcome.